Stock Market Efficiency and Momentum Effect:Evidence from Chinese Stock Market - Zheng, Huiyi (2020)
The main purpose of this dissertation is to investigate the market of efficiency of Chinese stock market. The test of market efficiency of Chinese stock market is through the direct examination of price random walk and the recognition of momentum or contrarian effect, which is the evidence of the market inefficiency. The combination of these two perspectives will provide a more comprehensive conclusion about the extent of Chinese market efficiency. The test of price movement shows that all four market has achieved the weak form market efficiency. But the momentum strategy applied in Shanghai and Shenzhen stock market shows a significant loss, suggesting the existence of contrarian effect. This result indicates that the extent of the market efficiency is relatively low compared to Small and Medium Enterprise board and Growth Enterprise Market. In addition, the contrarian effect is significant in all four markets in the bull period around year 2015. It is possible that the appearance of the momentum or contrarian effect is affected by the length of time selected. The momentum effect between different industries has higher possibility to appear in longer forming and holding period.